A Short Review on Growth and Endocrine Long-term Complications in Children and Adolescents with β-Thalassemia Major: Conventional Treatment versus Hematopoietic Stem Cell Transplantation: Growth and Endocrine Long-term Complications in thalassemia major after bone marrow transplantation - Ahmed, Shayma; Soliman, Ashraf; De Sanctis, Vincenzo; Alaaraj, Nada; Alyafei , Fawzia; Hamed, Noor; Yassin, Mohamed (Acta Biomedica Atenei Parmensis, 2022)
The conventional treatment of β-thalassemia (β-TM) patients is based on the correction of anemia through regular blood transfusions and iron chelation therapy. However, allogeneic hematopoietic stem cell transplantation (HSCT) remains the only currently available technique that has curative potential. Variable frequency and severity of long-term growth and endocrine changes after conventional treatment as well as after HSCT have been reported by different centers. The goal of this mini-review is to summarize and update knowledge about long-term growth and endocrine changes after HSCT in patients with β-TM in comparison to those occurring in β-TM patients on conventional treatment. Regular surveillance, early diagnosis, treatment, and follow-up in a multi-disciplinary specialized setting are suggested to optimize the patient's quality of life (www.actabiomedica.it).